STAGES AND ANALYSIS OF THE DEVELOPMENT OF THE NATIONAL ECONOMY - Tokhtamurotov Akhmadali (Galaxy International Interdisciplinary Research Journal, 2022)
This scientific article presents the stages of development of the national economy of our country and gives broad coverage.